BENTURAN NARASI DAN IDEOLOGI IRAN-ISRAEL DALAM TEORI SOSIAL BARAT DAN KONSEP ISLAM - Zaenal Abidin (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2025)
The Iran-Israel conflict is one of the most complex and potentially destabilizing geopolitical disputes in the Middle East, rooted in macro-injustice, humanitarianism, power struggles, religious ideologies, and deep historical mistrust. This scientific article seeks to analyze the dynamics of this conflict through the perspectives of Western and Islamic social theories. This research examines how Western theoretical frameworks, as well as Islamic concepts and paradigms and values, provide different understandings of the root causes of war conflicts. The analysis shows that while Western theories often emphasize power calculations, state security, the structure of the international system, and identity, Islamic social theories place a strong emphasis on religious identity, balanced power, theological perspectives on justice, and humanity.